The Cachoeira Tales and Other Poems - Nelson, Marilyn, 1946- (Book collections on Project MUSE., 2005)
" ... In "The Cachoeira tales" longing to take her family on a journey to "some place sanctified by the Negro soul," the poet finds herself in Brazil's Bahia, along with a theater director, a jazz musician, a retired commercial pilot, an activist, a university student, and two mysterious African American women whom they meet along the way. In rhymed couplets, each pilgrim tells a story, and the result is a rollicking, sensual exploration of spirit and community, with a nod to Chaucer and to traditional Trickster tales."--Dust jacket flap